Growth, Reproduction and Milk Yield of Holstein Friesian Heifers Born and Adapted in Kuwait - Razzaque, M.A.; Mohammed, S.A.; Al-Mutawa, T.; Bedair, M. (Pakistan Journal of Nutrition, 2009)
Kuwait’s dairy producers import pregnant Holstein Friesian Heifers and they thrive for 2.3 lactations with poor milk yield. Offspring of imported dams are subjected to high mortality, poor growth and reproduction. This study investigated growth, reproduction, milk yield and composition of locally born heifers fed two types of diets. Total 92 weaned 90 d old heifers born in Kuwait from imported dams were assigned to two different diets. Control (C): 25 heifers were fed commercial diet and Treatment (T): 67 heifers were fed balanced improved diets containing 17.5% and 15.1% CP, respectively. T diet was also balanced with vitamins and minerals, where, as C diets were not. Both herds were individually monitored for their heights and live weights; followed by reproductive and lactation performance. Herd T gained significantly (p<0.05) better live weight (T: 0.88 Kg vs. C: 0.71 Kg/h/d) than that of C and reaching significantly (p<0.01) better heights (T: 59% vs. C: 15%) of total standard height of 132 cm. Farm to farm differences in first service (mean±SD) conception rate and pregnancy rate did not differ between C and T herds (p = 0.05). Milk yield differences for C and T herds were 16.86±0.70 and 18.30±1.40 L/cow/day, respectively as well as Milk composition were not significant (p= 0.05). Milk Urea Nitrogen (MUN) concentration was significantly higher (p<0.001) in T herd than that of C reflecting a better protein nutritional status in T than that of C herd.